Atypical Presentation of Parkinson's Disease-Corticobasal degeneration (Journal of Dhaka National Medical College & Hospital, 2019)
Corticobasal degeneration (CBD) is a sporadic, rare, slowly progressive disorder with a clinical asymmetrical onset characterized by apraxia, dystonia, postural instability and akinetic-rigid syndrome that does not respond to levodopa. CBD usually presents at mid to late adult life. We describe an example of this rare case after taking consent from patient. A 45 years old women initially presented with walking difficulties and involuntary movement and pain in the left side. Previously she was diagnosed as a case of Parkinson's disease but was unresponsive to drug. On examination, she presented with left upper limb fixed dystonia, spasticity in all four limbs. Brain MRI showed asymmetrical cortical atrophy in the left frontotemporal cortex. Neuropsychological examination showed an impairment in visuospatial functioning, frontal-executive dysfunction. This case demonstrates that association of asymmetrical focal cortical (apraxia, dementia, progressive nonfluent aphasia) and subcortical features (bradykinesia, tremor, asymmetrical limb dystonia, gait disorder) remains the clinical hallmark of this condition. There are no absolute markers for the clinical diagnosis that is complicated by the variability of presentation involving also cognitive symptoms that are reviewed in the paper.J. Dhaka National Med. Coll. Hos. 2019; 25 (01): 53-56